Agronomic biofortification of maize (Zea mays L.) with zinc by using of graded levels of zinc in combination with zinc solubilizing bacteria and Arbuscular mycorrhizal fungi. (12th November 2020) - Suganya, A.; Saravanan, A.; Baskar, M.; Pandiyarajan, P.; Kavimani, R.
Abstract: Field experiment was conducted in black and red soils in order to study agronomic biofortification of Maize with Zinc using Arbuscular Mycorrhizal (AM) fungi and Zinc Solubilizing Bacteria (ZSB) in combination with graded levels of ZnSO4 . Treatment consisted of two factors viz., microbial inoculation (M1 : control, M2 : AM fungi, M3 : ZSB and M4 : M2 +M3 ) and graded levels of ZnSO4 (S1 : 0, S2 : 12.5, S3 : 25, S4 : 37.5, S5 : 50 Kg ha −1 and S6 : 0.5% foliar spray @ 45 and 65 DAS) replicated three times in Randamized Block Design . Application of AM fungi and ZSB in combination with 50 Kg ha −1 of ZnSO4 had recorded enhanced Zn content of maize grain to a tune of 25.9 and 26.6 ppm respectively under black and red soil which contributed to an increase of 22.0 and 21.4% over the absolute control. AM fungi and ZSB in combination with 37.5 Kg ha −1 of ZnSO4 had highest Zn content of maize grain and an increase of 10.4 and 10.6% respectively were recorded for black and red soil over the control. The highest grain Zn content was observed in S5 (ZnSO4 @ 50 kg ha −1 ) and the increase was 15.6 and 15.2% respectively for black and red soil followed by 37.5 (S4 ), 25 (S3 ), 12.5 Kg ha −1 of ZnSO4 (S2 ) and 0.5% foliar spray @ 45 and 65 DAS (S6 ) over control but the increase was not appreciable beyond 37.5 kg ha −1 (S4 ) in black soil.